Copper-zeolite integrated stormwater biofilter for nutrient removal – the impact of intermittent wetting and drying conditions. Issue 1 (10th December 2020) - Li, Yali; Deletic, Ana; McCarthy, David T.
Abstract: A large-scale column study was conducted to examine the sediment and nutrient removal performance of stormwater biofilters that contained layers of novel copper-zeolite filter media. The filters were exposed to stormwater under varied dosing frequency over 33 weeks and were assessed for their hydraulic performance and their efficiency in removing sediment and nutrients. The non-vegetated sand filters with layers of copper-zeolite media (SCu filters) achieved consistently good removal of total phosphorus (87%) despite the challenging dry-wet cycles, and the effluent concentration met a long-term irrigation guideline (0.05 mg/L). The same design achieved 51% removal of total nitrogen above the Australian runoff quality load reduction targets (45%). Incorporation of Leptospermum continentale into the copper-zeolite filters (LCCu-T) maintained the phosphorus removal (86%) and led to a slight increase in total nitrogen removal (57%). Both designs maintained good water permeability (200 mm/h at the end of the last wet period). Copper-zeolite played a mixed role in the system: enhancing nutrients removal through precipitation and ion exchange, maintaining high water permeability, limiting the advantages of vegetation on nutrient removal. Future studies should refine biofilter design and vegetation selection to augment the performance of copper-zeolite filters by integrating the advantages of vegetation on nutrient removal. Highlights: The first study investigating nutrient removal by copper-zeolite integrated stormwater biofilters. Consistently higher total phosphorus removal during 33-week operation with intermittent dry periods. Varied performance in the presence of different vegetation species. Adequate hydraulic performance of vegetated biofilters. Graphical Abstract